2014
DOI: 10.4103/1119-3077.127543
|View full text |Cite
|
Sign up to set email alerts
|

Nitrate and drinking water from private wells: Will there be an epidemic of cancers of the digestive tract, urinary bladder and thyroid?

Abstract: High nitrate levels drinking water is dangerous to health and can cause methemoglobinemia in children. It may also increase cancer risk in adults because nitrate is endogenously reduced to nitrite and subsequent nitrosation reactions give rise to N-nitroso compounds (NOCs), which are highly carcinogenic and can act systemically.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 13 publications
(25 reference statements)
0
9
0
Order By: Relevance
“…Drinking water that contains excess nitrates could pose a serious health hazard to the consumers, and is particularly a risk factor for developing many cancers (EPA, 2014;Njeze et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Drinking water that contains excess nitrates could pose a serious health hazard to the consumers, and is particularly a risk factor for developing many cancers (EPA, 2014;Njeze et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…In drinking water, a nitrate level of up to 3 mg/l is generally believed to be safe for drinking (Alhassan and Ujoh, 2012). Regulation of drinking water quality is so important that the United States Congress passed the safe drinking water act in 1974 (Njeze et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Elevated concentrations of nitrate and chloride in groundwater above WHO guidelines was linked to on-site sanitation in urban centres (Wright et al 2013). A high mean nitrate concentration of 31 mg/L reported in groundwater sources was predicted to be associated with thyroid and cancer risks (Njeze et al 2014) though direct measurement of this association and health outcomes is lacking in urban SSA. One study found presence of urinary mercury as evidence for inorganic mercury absorption in exposed populations (associated with airborne exposure pathways) although no long-term health impacts were investigated in this study (Dalvie and Ehrlich 2006).…”
Section: Inorganic/toxicitymentioning
confidence: 99%
“…Increased prevalence of hypertension in urban areas in Guinea observed by Balde et al (2006) point to the over-arching role of socio-economic factors (Balde et al 2006;Fourcade et al 2007;Damorou et al 2008;Griffiths et al 2012). Just two WASH studies in urban SSA considered cancer risks related to WASH factors (Njeze et al 2014;Bempah and Ewusi 2016), referred to in the previous section regarding inorganic and toxicity reviews. One study considering people living with epilepsy (PWE) and WASH access as part of a broader review of social function found that 95% of PWE did not encounter any difficulties in social functioning (including access to WASH).…”
Section: Chronic Non-communicable Diseasesmentioning
confidence: 99%
“…On the other hand, denitrification cycle still continues in cities with improper disposal of sewage through absorption wells, mainly leading to continuous production and dissemination of nitrate to groundwater (16). Previous studies show that high levels of nitrate in drinking water could be observed in areas with traditional wastewater treatment methods and industrial cities (due to the infiltration of sewage and industrial waste to groundwater) (17)(18)(19) …”
Section: Introductionmentioning
confidence: 99%